Two Cases and Review of the Literature: Primary Percutaneous Angiography and Antiplatelet Management in Patients with Immune Thrombocytopenic Purpura. (29th December 2013) - Torbey, Estelle; Yacoub, Harout; McCord, Donald; Lafferty, James
Abstract : We report two cases of immune thrombocytopenic purpura (ITP) associated with acute coronary artery syndrome highlighting the interventions done in every case along with the medications used during intervention and as outpatient. The first case is that of a woman with ITP exacerbation while on dual antiplatelet therapy and the second case is that of a male presenting with non-ST elevation myocardial infarction (NSTEMI) while in a thrombocytopenic crisis. In both cases antiplatelet therapy was held and thrombopoietic therapy was initiated before resuming full anticoagulation and coronary intervention. Given the paucity of data on ITP and antiplatelets treatment in the setting of acute coronary syndrome, no strict recommendations can be proposed, but antiplatelets appear to be safe acutely and in the long term in this category of patients as long as few measures are undertaken to minimize the risks of bleeding and thrombosis.